Social and scientific disorder as epistemic phenomena, or the consequences of government dietary guidelines. Issue 3 (23rd October 2018) - Scheall, Scott; Butos, William N.; McQuade, Thomas
Abstract: We begin with a process-oriented model of science according to which signals concerning scientific reputation serve both to coordinate the plans of individuals in the scientific domain and to ensure that the knowledge that emerges from interactions between scientists and the environment is reliable. Under normal circumstances, scientific order emerges from the publication–citation–reputation (PCR) process of science. We adopt and extend F. A. Hayek's epistemology according to which knowledge affords successful plan-based action and we employ this in the development of an epistemic theory of social order . We propose that external interferences with the PCR process have distorting effects on scientific knowledge and, thus, on scientific and social order more broadly. We support this claim by describing the history of the US federal government's development of standardized dietary guidelines for American consumers and its concomitant interference in the PCR process of nutritional science. We conclude that this interference contributed to social dis order in dietary science and beyond.